Plant Science - Kumar Dhal, Nabin; Charan Sahu, Sudam (IntechOpen, 2012)
The book "Plant Science" consists of 12 chapters divided into three sections authored by many researchers from different parts of the Globe. Section-I: Plant and Environment, describes the relationship between plants and environment, particularly enumerating species-environment relationship and response of plants to different environmental stress conditions. Section-II: Plant-Microbe relation, embodies broadly on both positive and negative aspects of microbes on plants. Section-III: Plant Biotechnology, shed light on current biotechnological research to develop modern technology for producing biologicals and also increasing plant immunity in present environmental conditions. The book "Plant Science" will be helpful to a wide group peoples; readers, scientists, researchers and allied professionals. We recommend it to you; enjoy reading it, save the plant and save life!